Doing development in West Africa : a reader by and for undergraduates - Piot, Charles (Online access with subscription: Duke University Press., 2016)
This unique collection contains essays by Duke University undergraduates in which they recount their experiences initiating small research and development projects in Togo. Of interest to students and teachers involved in service learning and study abroad, Doing Development in West Africa provides a relatable and intimate look into student-initiated development projects.